Agro-industrial waste: a cost-effective and eco-friendly substrate to produce amylase - Naik, Bindu; Kumar, Vijay; Rizwanuddin, Sheikh; Chauhan, Mansi; Gupta, Arun Kumar; Rustagi, Sarvesh; Kumar, Vivek; Gupta, Sanjay (Food production, processing and nutrition, 2023)
The increase in the global population has led to a substantial increase in the demand for food supply as well as food manufacturing industries that regularly produce large amounts of food waste. Agro-industrial waste has attracted tremendous attention all over the world since ancient times, such waste is usually dumped or burned and poses a threat to human health and the environment, which has always been a matter of serious concern. However, food waste is a major source of complex carbohydrates, proteins, lipids, vitamins, minerals, fibers, and helps in the manufacture of raw materials for a variety of industrial purposes such as the production of biofuels, enzymes, bioactive compounds, biodegradable plastics, surfactants. Hence it is necessary to convert food waste into value-added products that reduce environmental problems. The present review paper attempts to outline and analyze the potential of agro-industrial residues as cost-effective substrates to produce the enzyme amylase using a wide range of microbial strains. Graphical Abstract